Relation of Circulating Resistin to Insulin Resistance in Type 2 Diabetes and Obesity: A Systematic Review and Meta-Analysis - Su, Kai-zhen; Li, Yan-run; Zhang, Di; Yuan, Jun-hua; Zhang, Cai-shun; Liu, Yuan; Song, Li-min; Lin, Qian; Li, Man-wen; Dong, Jing (Frontiers in Physiology, 2019)
Background: Resistin, a cysteine-rich polypeptide encoded by the RETN gene, which plays an important role in many mechanisms in rodent studies, including lipid metabolism, inflammation and insulin resistance. Nevertheless, the relationship between resistin and insulin resistance in humans is under debate. The present study was designed to clarify the correlation between resistin and insulin resistance. Methods: A systematic literature search was performed using PubMed, Embase and Cochrane Library until March 3, 2019 with the keywords ‘resistin’ and ‘insulin resistance’. Funnel plots and Egger’s test were used to detect publication bias. A random-effects model was used to calculate the pooled effect size. Subgroup analysis and meta regression was performed to identify the sources of heterogeneity. Results: Fifteen studies were included in our systematic review. Among them, 10 studies with Pearson coefficicents were used for meta-analysis. We found resistin levels were weakly correlated with insulin resistance in those with T2DM and obesity (r = 0.21, 95% CI: 0.06–0.35, I2 = 59.7%, P = 0.003). Nevertheless, subgroup analysis suggested that circulating resistin levels were significantly positively correlated with insulin resistance in individuals with hyperresistinemia (≥14.8 ng/ml) (r = 0.52, 95% CI: 0.35–0.68, I2 = 0.0%, P = 0.513). And there was no relationship between circulating resistin and insulin resistance in those with normal circulating resistin levels (<14.8 ng/ml) (r = 0.08, 95% CI:-0.01–0.18, I2 = 0.0%, P = 0.455). Publication bias was insignificant (Egger’s test P = 0.592). Conclusion: In T2DM and obese individuals, resistin levels were positively correlated with insulin resistance in those with hyperresistinemia, but not in those with normal circulating resistin levels.